Effect of Bakers Yeast, Vitamin B12, and Vitamin C as Nutritional Improvement of Food on the Density Production of Brachionus plicatilis - Diana Chilmawati; Suminto Suminto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
The important factor of seedling production is live food with good quality. One way to improve quqlity of live food, Brachionus plicatilis, to gain a high quality of larvae in seedling production, is through implementing food enrichment. Chlorella sp, which is its live food, can be enriched by combination of baker’s yeast, vitamin B12 and vitamin C, which then given, in order to increase Branchionus plicatilis growth and nutrition content. Purpose of this study is to acknowledge comparative population growth and improvement of Brachionus plicatilis with different kinds of foods enrichment, to understand the right food enrichment composition for Brachionus plicatilis growth. This research are laboratory experimental, with 10 ind/ml early spread density on 5 litres capacity container. The experiment using a Completely Randomize Design with 4 treatment and 3 repetitions. That four treatments included A (Chlorella sp), B (Chlorella sp + baker’s yeast), C (Chlorella sp + baker’s yeast + vitamin B12), D (Chlorella sp + baker’s yeast + vitamin B12 + vitamin C). Result from the research shows that implementation of food enrichment, which using baker’s yeast, vitamin B12 and vitamin C, brings about a great significant differences (p<0,01) in each treatment to population growth. D is the best treatment with specific growth rate of 0,661, maximal density of 530,4 ind/ml and final density of 381,7 ind/ml. Key Words: Elements of Food Enrichment, Population, Brachionus plicatilis